Comparative Analysis of Ict in Public-Private Systems: The Ohim Case in the European Union and the Internal Revenue System in Chile - Cordova-Gonzalez, F; Duran-San Martin, C (Elsevier B.V., 2014)
This study presents a comparative analysis of Information and Computer Technology (ICT) integration in two organizations that combine public and private roles: Office for Harmonization in the Internal Market (OHIM) in the European Union (EU) and the Internal Revenue System (IRS) in Chile. The former registers trademarks and designs in the EU, the latter audits enterprises and individuals in the State of Chile, supervising their compliance with tax laws. Expert knowledge for both institutions is assumed as an organizational asset. Accordingly, OHIM experts and IRS auditors systematically introduce ICT tools for e-government and collaborative work, which is manifest through network and strategic alliances. This study also provides analysis concerning their functions and operations with the integration of ICT, identifying the critical aspects of the technological integration process through SWOT analysis. Then, the Corporative, Business, and Operational Levels frame the criteria for comparing both organizations taking as points of reference outcomes in productivity, effectiveness and efficiency, where the most outstanding differences and similarities are described. Among those critical factors analyzed, governance and coordination issues, budget allocation, and the decision-making process between public-private actors are prominent, as well as their Chiefs leadership, business models applied, processes quality, and knowledge management. Finally, the paper considers some tendencies shared by both organizations where the development of ICT goes hand in hand with business models based on human capital, transparency, collaboration among agents and relations with citizens. © 2014 Published by Elsevier B.V.